2017
DOI: 10.1016/j.pmedr.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Discordance in perceived risk and epidemiological outcomes of prostate cancer among African American men

Abstract: As guidelines for prostate cancer screening have changed from an annual screening recommendation starting at age 50 to discussing the benefits and harms of screening with health care providers, it is necessary to examine other types of factors that are important to prostate cancer screening decisions among African American men. Perceived risk of developing cancer has been shown to predict cancer control behaviors and is lower among African Americans. We characterized perceived risk of developing prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Similarly, in an educational intervention among African American men, Rice et al 55 found that the men ( n = 198) did not believe they were at increased risk of developing prostate cancer. Perceived risk was associated with lower income, hypertension, and beliefs about the association between race and cancer risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in an educational intervention among African American men, Rice et al 55 found that the men ( n = 198) did not believe they were at increased risk of developing prostate cancer. Perceived risk was associated with lower income, hypertension, and beliefs about the association between race and cancer risk.…”
Section: Resultsmentioning
confidence: 99%
“…In order for men to engage in an informed decision‐making process around prostate cancer early detection, they must be knowledgeable about the pros and cons of prostate cancer early detection, their risk of prostate cancer, and treatment options if they are diagnosed with the disease. Studies found that knowledge of prostate cancer was particularly low among older, less‐educated, lower‐income, and unmarried men 3,6,17,20,28,55 . Low‐income men may be less able to pay the deductible or copayment for healthcare visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research conducted at the MUSC Transdisciplinary Collaborative Center in Precision Medicine and Minority Men's Health has shown that AA men are not likely to believe that they are at increased risk for developing prostate cancer, despite African ancestry being one of the only established risk factors for disease (Society, 2015). In a community-based sample of AA men, for instance, only 28% reported that they were at high risk for developing prostate cancer, and 72% indicated that they were at the same or lower risk of developing PCa compared to men who were the same age (Rice et al, 2017). Heightened perceived risk of PCa was associated with income, having a personal history of hypertension, and beliefs about the association between race and cancer risk.…”
Section: Potential Causes Of Racial and Ethnic Disparitiesmentioning
confidence: 95%
“…Furthermore, a combination of ERG mRNA and PCA3 showed improved diagnostic value over serum PSA among CA patients. [ 24 ] Dr. Shrivastava also explained his collaborative studies with Genomic Health Oncotype DX. Together, they are exploring gene expression studies on non-DRE urine exosomes isolated from CA ( n = 55) and AA ( n = 36) PCa patients.…”
Section: Session 2: Prostate Cancermentioning
confidence: 99%